Nano-Coral Gold (NCG) Electrode for Electrochemical Determination of Arsenic (III) in Industrial Wastewater by Square Wave Anodic Stripping Voltammetry (SWASV). (2nd November 2022) - Yang, Lan; Sun, Leilei; Song, Jie; Zhao, Xueliang; Pan, Xicai; Wu, Zeming; Cai, Qingyun
Abstract: The motivation of this work is to develop a simple method for the on-site detection of total arsenic at the ppb level. For this purpose, novel nano-coral gold (NCG) was fabricated using NH4 Br to lead the growth of Au along a definite direction on a gold substrate. Square wave anodic stripping voltammetry (SWASV) was used for the determination of arsenic in industrial water with a NCG working electrode. Due to the high specific surface area and nano-structure of the nano-coral gold, high sensitivity was achieved with a limit of detection (LOD) of 0.4 ppb. 3.2 ppb arsenic was determined in industrial water. The detectable arsenic concentration is far below the regulatory limit of 10 ppb by the World Health Organization (WHO). Across the As (III) linear range from 2.5 to 100 ppb, the sensor response is stable, reproducible, and linear with concentration.